Depression and bedtime procrastination: Chain mediation of brooding and perceived stress - Xiaoxu Hou; Jinsheng Hu (Heliyon, 2023)
This study aimed to investigate the relationships between depression and bedtime procrastination (BP), and the mediating effect of the brooding and perceived stress (PS). Based on the self-regulatory failure theory of procrastination in a temporal context and response styles theory, we constructed a chain mediation model. Total of 1136 participants (389 males and 747 females) completed the online questionnaire. In the present study, the participants were asked to fill The Beck Depression Inventory-II (BDI-II), Bedtime Procrastination Scale (BPS), Perceived Stress Scale (PSS) and Ruminative Responses Scale (RRS). The results showed that high level of depression positively affected brooding, and high level of brooding further positively affected PS, thus leading to BP. However, we did not find the mediating effect of brooding between depression and BP. This indicated that mood plays an important role in the mechanism of depression's effect on BP. The findings revealed pathways between depression and BP and was of great significance for the intervention of BP.